The effectiveness of smoothed bonus portfolios for mitigating investment risk in defined contribution pension funds - Beyers, Frederik Johannes Conradie (University of Pretoria, 2022)
Dissertation (MSc (Actuarial Science))--University of Pretoria, 2018.